What kind of place is Norden? The image of Norden in Polish literary reviews of Nordic literature - Schab, Sylwia Izabela (Folia Scandinavica Posnaniensia, 2023)
The article discusses the question of how Nordic literature in translation – as reflected in Polish literary reviews – creates Norden as a place. What kind of imagery (constructed in a continuous discursive process) is projected on the Nordic region, and what purposes does this construction serve? The analysis draws on an understanding of place as a construct based on “body, landscape and culture” (Ringgaard & DuBois 2017:20) and uses concepts taken from imagology and literary reception studies.